INTEGRATED VIBRATION STUDY FOR NEW DESIGN POLAR ICEBREAKER. - NOONAN KNOPFLE AND FELDMAN SILVER SPRING MD (1967)
The scope of the study includes an estimate of propeller exciting forces, an estimate of the principal hull criticals of vertical, athwartship and torsional modes of vibration and a prediction of the relative importance of the various modes of hull vibration. A detailed analysis of the lateral, torsional and longitudinal vibration characteristics of the propulsion system is also provided, together with suitable recommendations for the optimization of the ship and machinery system parameters to minimize the resulting vibration. Other aspects are considered, such as the influence of ice-hull interaction, in so far as the state of the art permits. (Author)